Content of Pedagogical Education in the Modern World: Meanings, Problems, Practices and Development Prospects - Aleksandr G. Bermus; Vladislav V. Serikov; Natalya V. Altynikova (Peoples' Friendship University of Russia (RUDN University), 2021)
The article examines modern ideas about the nature of pedagogical activity, providing a critical analysis of the state of practice and scientific research on the problems of pedagogical education and reconstructing a set of methodological ideas, concepts and schemes related to ideas about the content and forms of pedagogical education. The authors present approaches to solving such problems as the modern understanding of the essence of pedagogical activity and the trends of its transformation in connection with the changed educational space, new functions of the teacher in the digital educational environment; crisis phenomena in pedagogical education and ways to overcome them. In this vein, the authors consider the concept of pedagogical education, substantiating its goals, content options and psychological mechanisms for mastering pedagogical activity. The proposed model of the process of professional socialization of teachers reveals the content, technologies and criteria for their effective professional training, dialectics of psychological, pedagogical and subject components in the structure of professional competence. Consideration is also given to the environment of a pedagogical university as a source of development of pedagogical experience and personal and professional qualities of teachers. The article may be of interest to researchers and organizers in the field of pedagogical education.